PROFIL PASIEN PENYAKIT MENULAR SEKSUAL PADA LAYANAN PRIMER TINGKAT I DI KOTA BANDAR LAMPUNG TAHUN 2015 - Linawati Novikasari; Analia Kunang; Vierto Irennius Girsang (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: Fast food is one that causes the risk of obesity and cause health problems. Nowadays, the occurrence of obesity in children tends to increase, and many other factors that can make obesity in children.Purpose: Knowing that factors associated with occurrence of obesity among student in Elementary School (Sekolah Dasar Negeri 2) Labuhan Bandar Lampung 2018Methods: This research was quantitative with cross sectional approach. Population in this research is all student at Elementary School (Sekolah Dasar Negeri 2) Labuhan Dalam Bandar Lampung with the sample of 63 respondents (simple random sampling).Results: Finding, genetic factor were 33 (52,4%) respondents with p-value 0,001, food intake factor 35 (55,6%) respondent with p-value 0,010 and physical activity factor 32 (50,8%) respondent with p-value 0,007.Conclusion: There is a relationship between genetic factors, food intake factor and physical activity factor with the occurrence of obesity among student in Elementary School (Sekolah Dasar Negeri 2) Labuhan Bandar Lampung 2018. Suggestion, this research could be used as base data, also need to do another research with number of respondent and different method. School management to report to public health services (Puskesmas) to provide nutritionist to give health education to student about obesity.